PRIMARY BILATERAL ADRENAL DIFFUSE LARGE B CELL LYMPHOMA: A CASE REPORT - Z, Nur Aisyah; AR, Rohaya; MS, Fatimah Zaherah; AG, Rohana (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Primary adrenal lymphoma of the adrenal gland is very rare and is identified in <1% of cases of non-Hodgkin's lymphoma. It is primarily bilateral but secondary involvement of the adrenal gland is typically unilateral. Diffuse large B cell lymphoma is the most common subtype, which represents 70% of cases. CASE We report a case of high-grade lymphoma of both adrenal glands found in a 77-year-old man. The patient was admitted to our hospital with progressively increasing pain and fullness in the right upper quadrant of his abdomen, generalised weakness and decreased appetite of 2 weeks’ duration. On examination, he had a blood pressure of 140/89 mmHg with no postural drop, a pulse rate of 90 beats/minute and no fever. His past medical history was significant for diabetes mellitus, hypertension and coronary artery bypass grafting 20 years ago. Computed tomography (CT) revealed adrenal gland measurements of 7.2 cm × 7.1 cm × 7.3 cm on the right, 5.1 cm x 4.4 cm x 5.1 cm on the left, with bilateral hypodense lesions associated with perilesional fat streakiness, Further laboratory workup revealed serum Na 131 mmol/L, serum K 5 mmo/L, haemoglobin 10.8 g/dL, white blood cell count 6.3 x 103/ µL, platelet count 267 x 109/L, erythrocyte sedimentation rate 37 mm/hour, early morning cortisol 371 nmol/L and LDH 547 U/L. The patient underwent CT-guided biopsy of the right adrenal. Histopathological test results showed a diffuse large B-cell lymphoma. Immunohistochemical stains were strongly positive for CD20 and LCA while negative for CD3, CD5, and cyclin D1. The patient’s Ki67 (Mib-1) index was approximately 90%. He was referred to a haematology centre for chemotherapy. CONCLUSION Primary bilateral adrenal non-Hodgkin’s lymphoma should be considered as the differential diagnosis of adrenal masses. It is extremely rare but rapidly progressive. Early diagnosis and treatment might dramatically affect the clinical outcome.